PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Mahasiswa Universitas Islam Malang Yang Menjadi Pengguna Transportasi Online Gojek) - Awaludin Arfan; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analyze the effect of service quality and trust on customer satisfaction who are Gojek users at the Islamic University of Malang. This study uses two independent variables, namely service quality and trust. With one dependent variable, namely customer satisfaction. After conducting literature and field reviews and formulating hypotheses, the data in this study were collected by distributing questionnaires to 50 people or students of the Islamic University of Malang who had used Gojek Indonesia online transportation as the research sample. The sampling technique used was purposive sampling.The data analysis method used is quantitative analysis, namely the validity and reliability test, classical assumption test, multiple linear regression analysis, t test and f test as well as the coefficient of determination. Based on data analysis, the results of this study are valid and reliable. In the classical assumption test, data is normally distributed, heteroscedasticity and multicolonierity do not occur. In the tangible hypothesis test, responsiveness, assurance and empathy do not have a significant effect on customer satisfaction. And the reliability hypothesis test has a positive and significant effect on customer satisfaction.Keyword : Service quality, trust, and customer satisfaction